Comparative invasion ecology of Carpobrotus from four continents: responses to nutrients and competition. (5th March 2022) - Portela, Rubén; Barreiro, Rodolfo; Alpert, Peter; Xu, Cheng-Yuan; Webber, Bruce L; Roiloa, Sergio R
Abstract: Two key hypotheses in invasion biology are that certain traits underlie invasiveness in introduced species, and that these traits are selected for during or after introduction. We tested these hypotheses by focusing on two traits likely to confer invasiveness, high increase in growth in response to increase in nutrients and low decrease in growth in response to competition. We compared four species of Carpobrotus that differ in invasiveness, using species from four continents: Africa, Australia, Europe and North America. To test for selection for these traits in Carpobrotus edulis, a highly invasive species, we compared plants from its native range in South Africa to plants from the other three regions, where C. edulis has been introduced. Plants were propagated in a common garden. Offspring were then grown alone with or without added nutrients, and together with another species of Carpobrotus or with the grass Ammophila arenaria (a co-occurring native species in Europe) without added nutrients. Response to nutrients did not differ between species of Carpobrotus, nor was competitive response less negative in more invasive species. However, increase in growth in response to added nutrients was greater in introduced than in native C. edulis . Moreover, fresh mass per ramet at the start of treatments was higher in the two invasive species than in the two non-invasive ones. We provide new evidence that introduction can select for response to nutrient enrichment in invasive species and add to the evidence for an association between size and invasiveness in introduced plants.